METODE GURU DALAM MENGEMBANGKAN KEMAMPUAN NILAI AGAMA DAN MORAL ANAK USIA DINI DI SEKOLAH - Haniya Haniya; Muhammad Turhan Yani; Achmad Sya’dullah (CV. ADIBA AISHA AMIRA, 2024)
Early Childhood Education (ECE) plays a crucial role in shaping the foundational character and morals of children. This study examines methods for developing religious and moral values in young children at school. The Library Research method was utilized, gathering information from national and international journals. ECE principles, including child needs, learning through play, conducive environments, integrated learning, life skills, instructional media, and gradual learning, are outlined. The moral development of young children follows Piaget's stages, influenced by religion, including the fairy tale, reality, and individual stages. Methods for developing religious and moral values through storytelling, play, field trips, and singing help children understand and apply these values in their daily lives. The research findings provide practical guidance for educators to effectively shape the character and morals of children. It is hoped that a deeper understanding of these methods will help create individuals of noble character ready to face future challenges